FRI0061 Cardiovascular risk factor and disease burden in belgian patients with rheumatic and musculoskeletal diseases of north african compared to european descent. (12th June 2018) - Fleurinck, F.; Tsang, L.; Walschot, M.; Reyskens, M.; Solomon, A.O.; Millen, A.; Dessein, P.
Abstract : Background: Patients with rheumatic and musculoskeletal diseases (RMDs) from developed populations often experience increased atherosclerotic cardiovascular disease (ACVD) risk. In European countries, increasing proportions of inhabitants originate in developing countries and are therefore reportedly at an earlier epidemiological transition stage, which is associated with reduced ACVD. 1 Objectives: This study aimed to determine whether population origin specific cardiovascular risk management is indicated in Belgian patients with RMDs. Methods: We recorded major conventional cardiovascular risk factors included in the Systematic Coronary Risk Evaluation (SCORE) or/and Framingham score equation, other conventional and non-conventional cardiovascular risk factor profiles and the prevalence of subclinical ACVD comprising arterial stiffness (pulse pressure >60 mmHg) and established ACVD (coronary artery disease, ischaemic cerebrovascular disease or/and peripheral artery disease) in 673 consecutive patients with RMDs; 126 and 547 were of North-African and European ancestry, respectively. Cardiovascular risk factors and disease were compared between patients of North African and European descent in multivariable logistic and linear regression models. Results: Patients of North African descent tended to have less frequently inflammatory RMDs (OR (95% CI)=0.69 (0.45–1.04)) including rheumatoid arthritis (RA) (OR (95% CI)=0.46 (0.19–1.09)), and had more often fibromyalgia (OR (95% CI)=2.93 (1.84–4.65)). Patients of North African descent were younger than their European descent counterparts (mean (SD)=47.5 (14.7) vs 55.7 (16.5) years, p<0.0001). In age, sex and inflammatory RMD adjusted analysis, North African descent patients had less prevalent hypertension (OR (95% CI)=0.54 (0.33–0.87)) and more frequent diabetes (OR (95% CI)=3.69 (2.00–6.80)); North African descent patients exercised ((OR (95% CI)=0.34 (0.20–0.57)) and used alcohol (OR (95% CI)=0.05 (0.02–0.12)) less often, and had a less frequent family history of ACVD (OR (95% CI)=0.64 (0.41–0.99)), smaller body height (mean (SD)=1.64 (0.09) vs 1.66 (0.11) m, p<0.0001) and larger the Arthritis Impact Measurement Scales Depression score (mean (SD)=4.4 (1.9) vs 3.7 (2.0), p=0.009). These findings translated into a frequencies of having ≥1 major cardiovascular risk factor, overall 10 year high risk for any (Framingham score ≥20) and fatal (SCORE ≥5) ACVD, and prevalence of subclinical and established ACVD that were as large in RMD patients from North African compared to European descent. European League Against Rheumatism multiplier 2 application in patients with RA did not alter these findings. Conclusions: Consistent disparities exist in ACVD risk factor profiles between RMD patients of North-African and European descent. However, the overall cardiovascular risk factor and disease burden is currently as large in RMD patients of North African compared to European ancestry. Adequate ACVD risk management in RMD patients should be performed irrespective of population origin. References: [1] Solomon A, et al. J Rheumatol2010;37:953–60. [2]. Agca R, et al. Ann Rheum Dis 2016;0:1–12. Disclosure of Interest: None declared